Supporting Junior Secondary Students’ Geometric Visualisation Through Augmented Reality and a STAR Scaffold: An Exploratory Pre–Post Pilot Study - Dinda Ayu Putri; Bulan Ainayya Fathiyyaturahma; Liffia Salwa Nabila (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Geometric visualisation is a fundamental yet challenging competency in mathematics education, particularly for junior secondary school students who struggle to interpret three-dimensional (3D) spatial structures using conventional two-dimensional instructional media. This study examines the effectiveness of Augmented Reality (AR) integrated with the STAR instructional strategy (Situation, Task, Action, Result) in enhancing students’ geometric visualisation skills. A quantitative pilot study employing a one-group pretest–posttest design was conducted with 9 eighth-grade students at SMP Muhammadiyah 3 Sukolilo, Indonesia, selected through purposive sampling. Data were collected using validated geometry visualisation tests administered before and after the intervention. The data were analysed using normalised gain (N-Gain) and paired sample t-test. The results indicate a significant improvement in students’ performance, with the mean score increasing from 20.00 (SD not reported due to small sample size) on the pretest to 88.89 on the posttest. The normalised gain score (g = 0.67) indicates a moderate-to-high improvement, while inferential analysis shows statistically significant differences (p < 0.05). The findings suggest that AR enhances spatial cognition by enabling interactive manipulation of 3D geometric objects, while the STAR strategy provides structured cognitive scaffolding that guides students through contextual problem understanding, task execution, and reflective learning. The novelty of this study lies in integrating STAR as a structured pedagogical scaffold within an AR-based spatial learning environment for geometry instruction in a low-resource classroom context. This study contributes to the growing body of evidence supporting immersive technologies in mathematics education, particularly for improving spatial reasoning in early secondary learners.